(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2023)
Acute pancreatitis (AP) is characterised by inflammation of the exocrine pancreas and is associated with acinar cell injury and both a local and systemic inflammatory response. AP may range in severity from self-limiting, characterised by mild pancreatic oedema, to severe systemic inflammation with pancreatic necrosis, organ failure and death. Most patients with acute pancreatitis have mild form of the disease about 20-30%develops a severe form ,often associated with single or multiple organ dysfunction requiring intensive care .the study is based upon the etiology ,epidemiology ,pathophysiology and advanced treatment of pancreatitis